Temporal influences on the prediction of postinfarction mortality by heart rate variability: a comparison with the left ventricular ejection fraction. Issue 6 (June 1994) - Odemuyiwa, O.; Poloniecki, J.; Malik, M.; Farrell, T.; Xia, R.; Staunton, A.; Kulakowski, P.; Ward, D.; Camm, J.
Abstract : OBJECTIVE–To examine the influence of the duration of follow up on the values of heart rate variability (HRV) and the left ventricular ejection fraction (LVEF) for predicting mortality after infarction. BACKGROUND–HRV is an index of autonomic balance that identifies patients at a high risk of arrhythmic events. The index is most depressed during the first few weeks after myocardial infarction whereas left ventricular function tends to deteriorate with time. HYPOTHESIS–The value of depressed HRV measured before discharge from hospital for predicting mortality after infarction should decline with time. METHODS–The HRV and the LVEF were assessed in 433 survivors of a first acute myocardial infarction: HRV < 20 units and LVEF < 40% were taken as cut off points. Kaplan-Meier survival functions for total cardiac mortality and sudden cardiac death were calculated for the whole five year follow up period and for different intervening periods. RESULTS–During follow up of four weeks to five years there were 46 (10.6%) deaths and 15 (3.5%) patients died suddenly. Within the whole follow up period, HRV < 20 units and LVEF < 40% were both strongly associated with total cardiac mortality (p < 0.0001), but HRV was an independent predictor of total cardiac mortality only during the first six months of follow up. There were no deaths predicted by HRV < 20 units after the first year of follow up whereas LVEF < 40% had a sensitivity of 43% and a positive predictive accuracy of 9% for predicting death during this period. HRV < 20 units was better than LVEF < 40% in predicting sudden deaths during the first year of follow up but was an independent predictor only of those sudden deaths occurring within six months of infarction. CONCLUSIONS–The duration of follow up affects the prediction of sudden death and total cardiac mortality from HRV. Reduced HRV as measured before discharge from hospital does not seem to retain independent prognostic value after six months of follow up. These findings have potential implications for the serial evaluation of HRV and for the prevention of sudden death after myocardial infarction.